Fully Inkjet‐Printed Stress‐Tolerant Microelectromechanical Reed Relays for Large‐Area Electronics. (29th February 2016) - Karim, Muhammed Ahosan Ul; Chung, Seungjun; Alon, Elad; Subramanian, Vivek
Abstract : Patterned deposition of solution‐processed materials utilizing printing technologies is a key enabler for the realization of low‐cost and large‐area electronics. While there have been several demonstrations of printed transistors, reports of printed MEMS have been generally sparse due to the difficulty in realizing robust printed suspended structures. Here, the first demonstration of fully inkjet‐printed three‐terminal microelectromechanical (MEM) reed relays offering excellent immunity to the mechanical stress variation often observed in printed cantilevers is reported. A novel MEM reed relay architecture is revealed where the upward curling of the printed reed due to the stress gradient in the film is restricted by a printed blocking reed, thus delivering immunity to stress variations. The printed reed relays show hyper‐abrupt switching with an on‐state resistance of only ≈15 Ω, immeasurable off‐state leakage, a switching delay of 32 μs, and stable operation over 10 5 cycles. An analytical model of the reed relay turn‐off voltage is developed, which is validated against the experimental results with varying reed relay geometrical parameters. The fully printed processing capability of the demonstrated reed relays in tandem with their stress tolerant nature and excellent device performance substantiates their promise as a new switching device for low‐cost and large‐area electronics. Abstract : A fully inkjet‐printed microelectromechanical relay based on a novel reed architecture is designed, fabricated, characterized, and modeled, and shows high on‐current, immeasurable off‐current, hyper‐abrupt switching, and good mechanical stability. The fully printed nature and stress‐tolerant features of this reed relay along with excellent device performances substantiate its promise as a future switching device for low‐cost and large‐area electronics.